Racje i sens „prawa do obrony” w procesie o nieważność małżeństwa - Gręźlikowski, Janusz (Prawo Kanoniczne, 2010)
“Right to defence” in canonical process for nullity of matrimony results first of all from natural right and it is strictly connected with the dignity of human being, recognition of which requires to respect and defend human’s rights. Each man has a right for defence. This right belongs to the rights related with human being and it precedes each codified statutory law. It is basic and fundamental right resulting form existence of other fundamental rights, protection of which should be guaranteed in the Church. Keeping this right is necessary for realization of justice and objectivity of the process. Norms of this law guarantee to the litigants inviolable right to defence in cases for nullity of matrimony, they promote this right and underline its importance and meaning as well as its precise application to clarify the truth of objectively conducted suit. Canon process law distinguish two distinctions: right to defence and exercising the right to defence. Litigants have the rights to defence guaranteed in all stages of the suit: starting the proceedings and initiation of dispute, in stage of showing the evidence, discussion as well as in decision stage and attacking the judgment phase. Exercising the right to defence the litigants can support themselves using such suit figures as: guardian, attorney in fact and lawyer. It is important, so as in the suit for nullity of the matrimony, a contention suit rule was kept, which requires keeping the right for defence to each litigant. These guarantees apply in special way to citation act, notifying about subject of dispute, possibility to present different evidence means, publishing the records of the case, presentation of applicable defences, publication of sentence and its appeal. Right to defence also allows the tribunal conducting the case to get to the truth about validity of questioned matrimony and to pass the sentence by the judge. Furthermore it guarantees to the faithful the right to know the truth about their matrimony. This right should be always interpreted in context of duty the litigants have regarding searching for objective truth about their marriage. This means guaranteeing to litigants their basic process rights.